Country Partnership Framework for Burkina Faso for the Period FY18-FY23 - World Bank Group (World Bank, Washington, DC, 2018)
This Country Partnership Framework (CPF) for the period FY18 to FY23, draws on the World Bank Group’s (WBG) 2017 Systematic Country Diagnostic (SCD) for Burkina Faso and feedback from in-country consultations with stakeholders. The SCD identified three top and seven second-tier priorities necessary to end extreme poverty and increase shared prosperity in Burkina Faso. These top priorities are: i) improving natural resource management; ii) promoting skills development, and iii) reducing gender bias against women. The second-tier priorities are: (i) building infrastructure to promote further local and regional integration; (ii) encouraging financial inclusion; (iii) increasing resilience through improved social protection to the poorest; (iv) ensuring fiscal efficiency and macroeconomic stability; (v) building up inclusive and transparent institutions; (vi) promoting competition and private sector development to stimulate efficiency and innovation; and (vii) managing urbanization with efficient urban centers. The SCD determined that the degree to which Burkina Faso achieves success will depend on its ability to facilitate economic transformation, expand the base of growth beyond the rapid expansion of the public sector, financed mainly by aid inflows and the booming mining sector – and share the positive impacts of economic growth with most citizens. This CPF follows the Burkina Faso Country Partnership Strategy (CPS) FY13-FY161 and builds on the Performance and Learning Review (PLR)2 completed in May 2015. This CPF recognizes the prevalent security context in the Sahel Region which suggests that traditional growth and poverty alleviation alone may not be sufficient to sustain peace and long-term stability in Burkina Faso. The wide range of Burkina Faso’s economic and social challenges will not be covered by this CPF. Rather, the proposed set of analytical, financial and advisory services will seek to build on existing operations where the WBG has a comparative advantage and where its transformational impact is greatest. Use of new IDA18 instruments, such as the Scale-up Facility (SUF), the Private Sector Window (PSW) and the Refugee Window, will also be prioritized. Partnership and collaboration with other development partners and regional development organizations, meanwhile, will be nurtured.